Ion-scale secondary flux-ropes generated by magnetopause reconnection as resolved by MMS - Eastwood,J; Phan,T; Cassak,PA; Gershman,DJ; Haggerty,C; Malakit,K; Shay,MA; Mistry,R; Oieroset,M; Russell,CT; Slavin,JA; Argall,MR; et al. (Geophysical Research Letters, 2016)
New Magnetospheric Multiscale (MMS) observations of small-scale (~ 7 ion inertial length radius) flux transfer events (FTEs) at the dayside magnetopause are reported. The 10 km MMS tetrahedron size enables their structure and properties to be calculated using a variety of multi-spacecraft techniques, allowing them to be identified as flux ropes, whose flux content is small (~22 kWb). The current density, calculated using plasma and magnetic field measurements independently, is found to be filamentary. Inter-comparison of the plasma moments with electric and magnetic field measurements reveals structured non-frozen-in ion behavior. The data are further compared with a particle-in-cell simulation. It is concluded that these small-scale flux ropes, which are not seen to be growing, represent a distinct class of FTE which is generated on the magnetopause by secondary reconnection.